Home Birth from a Comparative Legal Perspective - Nagy, Zsófia (Essays of Faculty of Law University of Pécs, Yearbook of [year], 2024)
The reproductive rights of women touch upon healthcare provided during childbirth, which involve freedom of choice of the place of childbirth. Thus, the issue of home birth is of interest among the legislators, which may be interpreted as part of an ”obligation” posed by international legal documents to ensure that respectful care is provided to women during the whole time of pregnancy. However, currently, there is no evident European consensus on how home birth shall be regulated thus, the legal approach is different among European states. The decision-making of the European Court on Human Rights has influenced domestic legislation, especially in Hungary (Ternovszky v. Hungary case), however, there was a completely different outcome in the Czech Republic in a factually very similar case (Dubská and Krejzová v. Czech Republic). Accurately, what is the woman’s role during childbirth? One model suggests that she is the passive side, and the physician has the main role in successfully conducting the birth. The other model follows the ideal, that childbirth is centred around the woman, and her competency in her body and mind makes her the one in control. Nevertheless, alternative birthing methods are not newfangled in some countries such as the Netherlands, where traditional midwife-supervised home birth can be carried out if a woman chooses so, unlike in Slovakia where this freedom of choice is not evident and discouraged by the legislators. This study tries to shed light on why legislation on this issue is so different in these European states.